Are There Limitations to Exercise Benefits in Peripheral Arterial Disease? - Zakari, Madaniah; Alsahly, Musaad; Koch, Lauren G.; Britton, Steven L.; Katwa, Laxmansa C.; Lust, Robert M. (Frontiers in Cardiovascular Medicine, 2018)
Substantial evidence exists indicating that inactivity contributes to the progression of chronic disease, and conversely, that regular physical activity can both prevent the onset of disease as well as delay the progression of existing disease. To that end “exercise as medicine” has been advocated in the broad context as general medical care, but also in the specific context as a therapeutic, to be considered in much the same way as other drugs. As there are non-responders to many medications, there also are non-responders to exercise; individual who participate but do not demonstrate appreciable improvement/benefit. In some settings, the stress induced by exercise may aggravate an underlying condition, rather than attenuate chronic disease. As personalized medicine evolves with ready access to genetic information, so too will the incorporation of exercise in the context of those individual genetics. The focus of this brief review is to distinguish between the inherent capacity to perform, as compared to adaptive response to active exercise training in relation to cardiovascular health and peripheral arterial disease.